Estudo da caracterização e influência do resíduo siderúrgico pó de balão em massas cerâmicas para produção de bloco estrutural cerâmico - GOMES, César Augusto de Oliveira (2019)
The metallurgical industry is an important sector within the Brazilian economy representing 1.26% of the national PIB. This industry generates a variety of solid wastes, liquid effluents and gaseous emissions in its various processing steps. One of the residues generated by the steel industry and the balloon powder that is formed by iron oxides in FeO, Fe2O3 e Fe2O4 forms. Balloon powder is still little used in attempts to reuse it as a co-product, although it can be pelleted by sintering and added to the raw materials in the blast furnace. In this way, the addition of waste in red ceramics is currently one of the main technological solutions for the final disposal of industrial solid waste. The incorporation of the balloon powder in red ceramic masses requires an analysis of chemical and mineralogical composition to obtain specific formulations that collaborate in the search of the improvement of the properties of the manufactured materials. The purpose of this study was to evaluate the effect of the incorporation of 5, 10 and 15% by weight of the residue of the balloon powder into a clay mass composed of strong clay and weak clay, for the production of a structural block ceramic.